2014
DOI: 10.2337/db14-0684
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal β-Cell Proliferation and Mass Expansion Is Dependent on the Transcription Factor Nkx6.1

Abstract: All forms of diabetes are characterized by a loss of functional β-cell mass, and strategies for expanding β-cell mass could have significant therapeutic benefit. We have recently identified the transcription factor Nkx6.1 as an essential maintenance factor of the functional β-cell state. In addition, Nkx6.1 has been proposed to control β-cell proliferation, but a role for Nkx6.1 in regulating β-cell mass has not been demonstrated. Here, we show that Nkx6.1 is required for postnatal β-cell mass expansion. Genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Nkx6.1 overexpression increases b-cell proliferation, GSIS, and cell survival [7][8][9]. While early studies from another group found no enhancement with Nkx6.1 [43], subsequent studies from the same group support our findings [44,45]. Nkx6.1 overexpression induces expression of the hormone VGF, which enhanced GSIS and increased b-cell survival [9].…”
Section: Discussionsupporting
confidence: 60%
“…Nkx6.1 overexpression increases b-cell proliferation, GSIS, and cell survival [7][8][9]. While early studies from another group found no enhancement with Nkx6.1 [43], subsequent studies from the same group support our findings [44,45]. Nkx6.1 overexpression induces expression of the hormone VGF, which enhanced GSIS and increased b-cell survival [9].…”
Section: Discussionsupporting
confidence: 60%
“…However, recent studies by Sander and colleagues have shown that Nkx6 . 1 is required for post-natal β-cell expansion [56] and maintenance of β-cell identity [57]. The effects of Nkx6 .…”
Section: Discussionmentioning
confidence: 99%
“…In the pancreas, NKX6.1 is exclusively expressed in b-cells and is required for prenatal b-cell development and function and postnatal b-cell expansion (17). In placenta, it remains to be studied whether the epigenetically controlled expression of NKX6.1 is a modulator of nutrient transfer and thus perhaps an indirect modulator of fetal b-cell development, insulin secretion, and fat mass.…”
Section: Discussionmentioning
confidence: 99%